2010
DOI: 10.3109/08958378.2010.519009
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological effects of emission particles from fossil- and biodiesel-fueled diesel engine with and without DOC/POC catalytic converter

Abstract: There is increasing demand for renewable energy and the use of biodiesel in traffic is a major option when implying this increment. We investigated the toxicological activities of particulate emissions from a nonroad diesel engine, operated with conventional diesel fuel (EN590), and two biodiesels: rapeseed methyl ester (RME) and hydrotreated fresh vegetable oil (HVO). The engine was operated with all fuels either with or without catalyst (DOC/POC). The particulate matter (PM(1)) samples were collected from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 43 publications
6
57
4
Order By: Relevance
“…Biodiesel (rapeseed oil methyl ester) has been shown to have four times higher cytotoxicity than conventional diesel under idling conditions, while no differences were observed for the transient state (Bünger et al, 2000). So far, the opposite was found by others: no differences for cytotoxicity with vehicle emissions under idling conditions (Jalava et al, 2010).…”
Section: Clinical and Toxicological Studiesmentioning
confidence: 78%
See 1 more Smart Citation
“…Biodiesel (rapeseed oil methyl ester) has been shown to have four times higher cytotoxicity than conventional diesel under idling conditions, while no differences were observed for the transient state (Bünger et al, 2000). So far, the opposite was found by others: no differences for cytotoxicity with vehicle emissions under idling conditions (Jalava et al, 2010).…”
Section: Clinical and Toxicological Studiesmentioning
confidence: 78%
“…This was particularly evident for mixtures of rapeseed and fossil diesel, suggesting that a mixture can lead to more harmful particulate emissions. So far, the opposite was found by others: no differences for cytotoxicity with vehicle emissions under idling conditions (Jalava et al, 2010).…”
Section: Changing Fuel Compositionmentioning
confidence: 86%
“…24,40,45,50 Although no universal pattern is observed, 11,24,25,40,43,49 many suggest that biodiesel particles may be more harmful to health than mineral diesel particles. For example, some older studies found that rapeseed biodiesel particles were more cytotoxic to mouse fibroblasts than mineral diesel particles, 25,42 and that particles collected from combusting an 80% mineral diesel : 20% biodiesel blend were more cytotoxic to human airway epithelial cells than either pure fuel alone.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…In terms of biodiesel use, studies indicate that biodiesel exhaust is significantly less mutagenic in comparison with diesel fuel [82,[84][85][86][87][88]. On the other hand, some studies reported no difference between diesel and biodiesel exhaust or nearly the same mutagenic effects [89,90].…”
Section: Mutagenicity and Genotoxicity Assessmentsmentioning
confidence: 99%
“…The studies found that biofuel presents a variable cytotoxicity compared to fossil fuels. In general, biodiesel presents an increase in cytotoxicity effects when compared to diesel fuel [82,93,99] or no significant differences in cytotoxicity between biodiesel and diesel exhaust [84,88]. A study carried out using ethanol added to gasoline fuel demonstrated a strong decrease of ethanol exhaust cytotoxicity potential compared to gasoline exhaust [100].…”
Section: Cytotoxicity Assessmentsmentioning
confidence: 99%